أثر العرف في تغیر الفتوى فقھ الأسرة – انموجا - حشیفة, أحلام; عبد اللاوي, نسیبة; خلوط, هناء (University of Eloued-جامعة الوادي, 2016)
تطبیقیة – والإشكال الرئیس الذي دارت علیه هذه الد ا رسة هو: ما أثر العرف في بعض الفتاوى المبنیة على أع ا رف ا زلت أو تغیرت؟ ومن خلال مباحث هذه الد ا رسة أ جی ب على هذا الإشكال وَفق مباحث كالآتي: المبحث الأول خصصناه لبیان مفهوم الفتوى من تعریف ودلیل لحجیتها، وكذا أسباب تغیر الفتوى وضوابط تغیرها، أما المبحث الثاني فجعلناه للعرف بتعریفه وعرض لأدلة حجیته بالإضافة إلى أقسامه وشروط اعتباره، وفي الجانب التطبیقي وضعنا ثلاث نماذج دخل العرف في تغیر الحكم فیها، وذلك من خلال المبحث الثالث وهي في ألفاظ الطلاق، النفقة والعدة. وتوصل البحث إلى جملة من النتائج من أهمها: إمكانیة تغییر بعض الأحكام والفتاوى بتغیر الأع ا رف أو زوالها والنماذج وضحت ذلك. Summary of the study: This research under the impact of the change in the title of custom fatwa "Fiqh of the family model" - the study of practical theory - The main forms, which took place upon this study is: What impact custom in some fatwas based on the norms of still or changed? Through this study Investigation answer to this dilemma according Investigation follows: The first topic dedicated to the statement of the concept of the fatwa from the definition of and guide to authentic, as well as the reasons for changing the fatwa and regulations change, and the second section Fjalnah to custom defined and presentation of evidence of its authority in addition to its divisions and conditions considered, and in the practical side we put three models custom entered in the change of government in which, through Section It is the third in the words of divorce, alimony, and the kit. The research found a number of outcomes including: the possibility of changing some of the judgments and opinions change norms or demise, forms, and sacrificed it .
مذكرة ليسانس
Keywords: العرف /الفتوى /فقه /الاسرة; Coutume/Fatwa/Jurisprudence/Famille